Initial growth of Coffea canephora: Simulation of organomineral system and Limnoperna fortunei as soil improvement - Barbosa, Mariana Cristina [UNESP]; Sena, Karla Nascimento [UNESP]; Maltoni, Kátia Luciene [UNESP] (Coffee Science, 2023)
The use of residues can be an alternative to mineral fertilization. Manures, sources of nutrients and organic matter, are successfully used in family farming. Another residue that can be used for soil acidity amelioration is the shell of the golden mussel (Limnoperna fortunei), which is rich in CaCO3. This work evaluated the contribution of ground golden mussel shells (GMS) in combination with cattle (CTM) and sheep (SHM) manure to the initial growth of Conilon coffee in an acidic sandy soil. The experiment was carried out in protected cultivation in pots (30 kg) with two Conilon coffee cultivars. The treat-ments consisted of two doses of CTM (0 or 67 t ha-1) and four doses of GMS (0, 1, 2 and 3 t ha-1), with three replications. Each treatment was incorporated into the soil before the introduction of the seedlings in the experimental units, and 60 days later, a dose of SHM was applied on the soil surface (20 t ha-1). After 180 days, the soil fertility was analysed, and the seedling height, stem diameter, root volume and fresh and dry mass of the aerial parts and roots were measured. Furthermore, the Dickson Quality Index (DQI) was calculated. Both the sheep and the bovine manure increased the pH, the contents of P, MO, K+, Ca2+, and Mg2+, and the cations exchange capacity (CEC) of the soil. The addition of GMS increased the pH and the Ca2+ content while reducing the potential acidity of the soil. A pH above 6.0 reduced the levels of micronutrients in the soil. The use of CTM and SHM shows promise in the initial growth of coffee seedlings (height-H, FMAP, fresh and dry mass of the aerial parts-DMAP, FAR, fresh and dry mass of the root system – DMR diameter, RV root volume and Dickson Quality Index). Ipiranga 501 surpassed Verdebras G35 in aerial fresh and dry mass, root volume and IQD, with or without the addition of 3 t ha-1 of ground GMS.
Keywords: Cattle manure; Conilon coffee; Golden mussel; Robusta coffee; Sheep manure